OVERVIEW OF DIGITAL TOOLS IMPLEMENTATION FOR OPERATIVE MONITORING OFTECHNICAL AND ENGINEERING OBJECTS - BODNARUK, VASYL; MELNYCHUK, STEPAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The main attention is paid to the functionality and aspects of the implementation of tools intended for operational monitoring of the dynamic state of technical and engineering facilities, in particular industrial equipment (electric motors, pumps, compressors) and building structures (bridges, supporting elements, high-rise structures). The features of the use of modern devices for analyzing vibration characteristics are described, which allows timely detection of deviations that may indicate technical malfunctions or structural wear processes.The popular types of such devices are considered, which differ in the measurement range, the presence or absence of an integrated data logger, the type of sensor, and the method of transferring information to a computer or cloud environment. The devices are analyzed depending on their purpose: models without memory and digital interfaces are effective for spot measurements and quick checks, while devices with the function of recording to an SD card or with a USB interface ensure that the obtained data is saved for further analysis. Particular attention is paid to devices that support integration with mobile applications, which significantly speeds up the exchange of information and makes monitoring available to multiple users at the same time. In addition, the advantages of using wireless technologies in such devices are considered, which contributes to greater mobility and simplifies their operation in conditions of limited access to the object.The criteria for selecting monitoring devices are defined according to the nature of the oscillations of the monitored object (medium or high frequencies), the need for data post-processing, and the level of personnel training. It is shown that such devices are not only measuring instruments, but also an important component of computerized maintenance systems, contributing to the reliability and efficiency of technological facilities. The article considers the prospects for the development of monitoring devices and their further application in various industries, taking into account their effectiveness in controlling the technical condition of facilities. In addition, the author emphasizes the possibility of using such devices in real time to promptly respond to changes in the condition of equipment and prevent possible emergencies.
Keywords: monitoring devices; geosensors; characteristics; geosignals